Practicing Antimicrobial Stewardship: De-Escalating Antibiotics in Patients With Acute Myeloid Leukemia and Neutropenic Fever. (21st April 2020) - Fuller, Risa; Moshier, Erin; Jacobs, Samantha E; Tremblay, Douglas; Lancman, Guido; Coltoff, Alexander; Caro, Jessica; Mascarenhas, John; Rana, Meenakshi
Abstract: We compared risk of recurrent fever in patients with acute myeloid leukemia undergoing induction chemotherapy with febrile neutropenia without an infectious source in which antibacterials were de-escalated before neutrophil recovery versus continued. There was less recurrent fever when antibacterials were de-escalated early with no increased adverse events.